2022
DOI: 10.1093/nar/gkac1091
|View full text |Cite
|
Sign up to set email alerts
|

NrnA is a 5′-3′ exonuclease that processes short RNA substrates in vivo and in vitro

Abstract: Bacterial RNases process RNAs until only short oligomers (2–5 nucleotides) remain, which are then processed by one or more specialized enzymes until only nucleoside monophosphates remain. Oligoribonuclease (Orn) is an essential enzyme that acts in this capacity. However, many bacteria do not encode for Orn and instead encode for NanoRNase A (NrnA). Yet, the catalytic mechanism, cellular roles and physiologically relevant substrates have not been fully resolved for NrnA proteins. We herein utilized a common set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(113 reference statements)
0
1
0
Order By: Relevance
“…The results revealed that DrRecJ-like efficiently hydrolyzes ssRNA to 1 nt, with the highest activity observed in the presence of Mn 2+ as a cofactor (Figure 3A ). This observation aligns with findings for homologs from other bacteria ( 12 , 14 , 38–40 ). Additionally, Ni 2+ , Co 2+ and Mg 2+ proved to be effective metal cofactors, while Zn 2+ and Ca 2+ exhibited inhibitory effects.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The results revealed that DrRecJ-like efficiently hydrolyzes ssRNA to 1 nt, with the highest activity observed in the presence of Mn 2+ as a cofactor (Figure 3A ). This observation aligns with findings for homologs from other bacteria ( 12 , 14 , 38–40 ). Additionally, Ni 2+ , Co 2+ and Mg 2+ proved to be effective metal cofactors, while Zn 2+ and Ca 2+ exhibited inhibitory effects.…”
Section: Resultssupporting
confidence: 91%
“…Unlike BsNrnA, which degrades 2–5 nucleotide long RNA oligomers from the 3′ end, and longer RNA substrates from the 5′ end ( 41 ), our data indicate that DrNrnA cleaves both nanoRNA and longer oligos in the 3′-5′ direction. On the contrary, it was reported that NrnA-like proteins from Thermus thermophiles HB8, Enterococcus faecalis and Streptococcus pyogenes prefer to digest substrate in a 5′-3′ direction ( 38 , 45 ). Further research is required to test whether those non-conservative amino acid variances mentioned above may result in distinct substrate sequence and length preferences, and cleavage directionality of these proteins.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Notably, PRC barrel proteins are often found in the vicinity of genes encoding translation systems components or RNA processing enzymes. Specifically, cdpB1 is encoded next to nrnA , a 5’-3’ exonuclease involved in processing of short RNA substrates 38 , and HVO_1964 is encoded divergently to infB , translation initiation factor 2. These two genes are located in conserved neighborhoods in haloarchaea (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%